The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1001/archdermatol.2010.368
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Pilot Study of the Effects of an Extra Office Visit on Adherence and Outcomes in Atopic Dermatitis

Abstract: Dr Hillhouse had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis. Study concept and design: Baker and Hillhouse. Acquisition of data: Hillhouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 6 publications
0
27
0
1
Order By: Relevance
“…This small, unblinded pilot trial, 373 powered to detect large differences in treatment effect, did not find any significant beneficial effect of one extra visit to the doctor. The trial also found no correlation between adherence and reduction in severity and no correlation between baseline severity and adherence, but the study was underpowered to exclude even moderate differences.…”
Section: Overall Implications For Research and Practicementioning
confidence: 66%
See 2 more Smart Citations
“…This small, unblinded pilot trial, 373 powered to detect large differences in treatment effect, did not find any significant beneficial effect of one extra visit to the doctor. The trial also found no correlation between adherence and reduction in severity and no correlation between baseline severity and adherence, but the study was underpowered to exclude even moderate differences.…”
Section: Overall Implications For Research and Practicementioning
confidence: 66%
“…All participants visited the clinician after 4 weeks of treatment. This pilot trial 373 found a significant improvement in eczema severity assessed by EASI scores, IGA score and participant-assessed itch in both groups, but there were no significant differences between those who had an extra visit to the clinician at 4 weeks and those who did not. The mean difference in percentage improvement in severity measured using EASI scores (extra visit group 76% vs. control group 45%; p = 0.06) showed some difference; however, only 26 out of the 30 participants randomised were included in the analysis.…”
Section: Studiesmentioning
confidence: 74%
See 1 more Smart Citation
“…Ausgehend von der mangelnden Compliance bei Hautpatienten beschreibt er gezielte und effektive Maßnahmen für eine offenere Haltung der Patienten gegenüber einer Cortison-Behandlung durch häufigere Konsultationen, schriftliche Informationen und das Eingehen auf die Ängste der Patienten. Gerade bei Neurodermitis scheint die gezielte Zuwendung und Aufklärung ein wichtiger Faktor zu sein, um die Therapieeffektivität zu gewährleisten [10,11].…”
Section: Fazit Für Die Praxisunclassified
“…Attempting to improve adherence to the treatment regimen is also important. One study found frequent follow-up visits may be one potentially useful strategy [ 56 ] .…”
Section: Therapeutic Overviewmentioning
confidence: 99%